What are they exactly? Are they similar or different? A Conceptual and Contextual Insights of Multilingualism and Plurilingualism from Indonesian EFL Classrooms - Devilito Prasetyo Tatipang; Anas Irwan; Syahrullah Syahrullah; Fajar Aswat (Journal of English Language Teaching, Literature and Culture, 2025)
This systematic literature review aims to clarify the conceptual distinctions and contextual applications of nbsp;multilingualism nbsp;and nbsp;plurilingualism nbsp;in Indonesian English as a Foreign Language EFL classrooms The study addresses widespread confusion among educators and policymakers by analyzing 25 high quality peer reviewed studies published between 2021 to 2025 Using rigorous selection criteria and thematic analysis the review found that nbsp;multilingualism nbsp;is typically understood as the coexistence of multiple languages within societies or institutions while nbsp;plurilingualism nbsp;highlights an individual s integrated and dynamic use of multiple languages Despite Indonesia s rich linguistic diversity national policies and curricula have yet to fully adopt plurilingual principles often favoring strict language separations Classroom research reveals that language practices are more fluid with teachers and students frequently combining languages for comprehension and engagement However varying teacher beliefs and insufficient training hinder the implementation of effective plurilingual pedagogy This study underscores the need for clear shared definitions and improved professional development to bridge the gap between theory policy and practice The findings advocate for policies and teaching approaches that recognize and harness the full linguistic repertoires of learners Ultimately this review provides a critical foundation for advancing multilingual education in Indonesia and contributes to global discussions on language pedagogy in multilingual contexts< em>< p>